Efficacy and safety comparison of liraglutide, glimepiride, and placebo, all in combination with metformin, in type 2 diabetes - Nauck, M; Frid, A; Hermansen, K; Shah, N; Tankova, T; Mitha, I; Zdravkovic, M; Düring, M; Matthews, DR (2009)
Objective- The efficacy and safety of adding liraglutide (a glucagon-like peptide-1 receptor agonist) to metformin were compared with addition of placebo or glimepiride to metformin in subjects previously treated with oral antidiabetes (OAD) therapy. Research design and methods- In this 26-week, double-blind, double-dummy, placebo- and active-controlled, parallel-group trial, 1,091 subjects were randomly assigned (2:2:2:1:2) to once-daily liraglutide (either 0.6, 1.2, or 1.8 mg/day injected subcutane-ously), to placebo, or to glimepiride (4 mg once daily). All treatments were in combination therapy with metformin (1g twice daily). Enrolled subjects (aged 25-79 years) had type 2 diabetes, A1C of 7-11% (previous OAD monotherapy for ≥3 months) or 7-10% (previous OAD combination therapy for ≥3 months), and BMI ≤40 kg/m2. Results- A1C values were significantly reduced in all liraglutide groups versus the placebo group (P < 0.0001) with mean decreases of 1.0% for 1.8 mg liraglutide, 1.2 mg liraglutide, and glimepiride and 0.7% for 0.6 mg liraglutide and an increase of 0.1% for placebo. Body weight decreased in all liraglutide groups (1.8-2.8 kg) compared with an increase in the glimepiride group (1.0 kg; P < 0.0001). The incidence of minor hypoglycemia with liraglutide (̃3%) was comparable to that with placebo but less than that with glimepiride (17%; P < 0.001). Nausea was reported by 11-19% of the liraglutide-treated subjects versus 3-4% in the placebo and glimepiride groups. The incidence of nausea declined over time. Conclusions- In subjects with type 2 diabetes, once-daily liraglutide induced similar glycemic control, reduced body weight, and lowered the occurrence of hypoglycemia compared with glimepiride, when both had background therapy of metformin. © 2009 by the American Diabetes Association.